The use of X-ray computed tomography in timber construction research - Couceiro, José; Hansson, Lars; Sehlstedt-Persson, Margot; Sandberg, Dick (Luleå tekniska universitet, Träteknik, 2016)
X-ray computed tomography (CT), which was introduced in the medical field in the early 1970s, is also a powerful tool for the non-destructive measurement of dynamic processes in wood. For more than 20 years, CT has been used in wood research at Luleå University of Technology. The uniqueness of the CT equipment means that processes such as drying, modification, water absorption, internal and external cracking and material deformation can be studied in temperature- and humidity-controlled environments. The data recorded by the CT during the process is converted into two- or three-dimensional images that for instance can show dynamic moisture behavior in wood drying.This paper gives an overview of the possibilities of using CT in timber construction research, and shows examples of applications and results which can be particularly difficult to achieve using other methods. A specific focus is on studies on wood products for construction, and how to deal with different material combinations such as wood and metal.The practical application of the result is that CT-scanning, combined with image processing, can be used for non-destructive and non-contact 3-D studies of exterior constructions elements during water sorption and desorption, to study swelling and shrinking behaviour, delamination phenomena, crack development, etc. Godkänd; 2016; 20160712 (dicsan)